Acceptance towards giving birth to a child with beta-thalassemia major - A prospective study - Yiu Man Chan; Oi Ka Chan; Yvonne Kwun Yue Cheng; Tak Yeung Leung; Terence Tzu Hsi Lao; Daljit Singh Sahota (Elsevier, 2017)
Objective: To explore the acceptance of pregnant Chinese women on giving birth to a child with beta-thalassemia major. Materials and methods: Women's acceptance on having a child with beta thalassemia major was assessed using standard gamble metrics during an interviewer-administered survey on 309 women recruited in the antenatal clinic. Utility scores were determined and the association with sociodemographic factors was assessed. Results: The median utility score for having a child with beta-thalassemia major was 0.5 (0-0.65). Women having either higher educational level or family income had significantly higher utility scores (P < 0.05) corresponding to a higher acceptance. During the interview 59.9% participants indicated that they would elect to undergo a termination of pregnancy if their fetus was diagnosed with beta-thalassemia major but 26.5% participants were unable to decide what action they would take. Conclusion: Many Chinese pregnant women are ambivalent about giving birth to a baby with beta-thalassemia major. Women with higher educational level or higher family income had a higher acceptance towards the condition.